Older Rural Americans - Youmans, E. Grant (Elmer Grant), 1907- (Book collections on Project MUSE., 1967)
Most social studies of older people in the United States have focused upon problems and conditions encountered in urban centers. In Older Rural Americans sixteen social scientists representing various regions examine in depth the circumstances of older people in rural America. The authors first consider older people in the contexts of work, the family, and the community, discussing their social outlook, their place in these contexts, and the profound changes they face as they move away from an active part in these areas of life. Later chapters analyze the distribution of the rural aged populat.